A Buffer Stock Model to Ensure Price Stabilization and Availability of Seasonal Staple Foods under Free Trade Considerations - Wahyudi Sutopo; Senator Nur Bahagia; Andi Cakravastia; T.M.A. Arisamadhi (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
Price volatility and scarcity have become a great problem in the distribution system of seasonal staple foods produced by the agricultural industry. There is a salient supply disparity during the harvest and planting seasons. This condition could cause disadvantages to stakeholders such as producers, wholesalers, consumers, and government. This paper proposes a buffer stock model under free-trade considerations to substitute quantitative restrictions and tariffs with an indirect market intervention instrument. This instrument was developed using a buffer stock scheme in accordance with a warehouse receipt system (WRS) and a collateral management system. A public service institution for staple food buffer stock (BLUPP) is proposed as the wholesaler's competitor, with as main responsibility to ensure price stabilization and availability of staple food. Multi-criteria decision-making is formulated as a single objective mixed integer non-linear programming (MINLP) model. The results shows that the proposed model can be applied to solve the distribution problem and can give more promising outcomes than its counterpart, direct market intervention.